(untitled) (Journal of the College of Basic Education, 2024)
Muhammad Musaddiq confronted to the foreign colonial powers which led by Britain, the United States, and the Soviet Union. The peak of this Resistance was represented by the nationalization of the Iranian oil and entering into a conflict with the Anglo-Iranian Oil Company which it was owned by the British government. Both Britain and the United States of America realized that the nationalization decision constituted a direct threat to their economic and political influence in the Middle East. They tried various means, including support of the political forces inside Iran once and the economic and commercial sanctions on Iran once again . all that as a means of pressure on Iran at time and a military threat at other times. The Americans and the British managed a coup against Musaddiq’s government and overthrow it, with the cooperation of the parties loyal to them and the Opposition to Musaddiq’s government, especially the religion men. Their Opponents and coup against Musaddiq provided the opportunity once again to impose their control over Iranian oil and all the region.